PEMBINAAN MUTU, PENGELOLAAN KEUANGAN DAN MEMBANGUN MENTAL USAHA UNTUK MENINGKATKAN TARAF HIDUP KEPULAUAN SERIBU - Dyah Puspitasari Sunaryo Putri; Syahreen Nurmutia; Niera Feblidiyanti; Khairunnisa Khairunnisa (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Entrepreneurship is an alternative in reducing poverty problem, by developing businesses or entrepreneurships that create jobs. Many people on the Untung Jawa island have become entrepreneurs to meet their daily lives. The problem arises in entrepreneurship is to maintain the quality of products and services, because one of the keys to business sustainability is the reliable products. Furthermore, maintaining the quality is important because it can reduce costs and prevent consumer disappointment that is caused by damaged product. In addition to controlling product quality, it is necessary to have good financial management because businesses that have a good marketing ability but have a poor financial management will fail and after that they will need to build a business mentality. The method used in quality development, financial management and mental building are through counseling, discussions and simulations method through the development and mentoring activities of the Kepulauan Seribu community with the theme of product quality development, financial management and building business mentality to improve the living standards of the Kepulauan Seribu community. From the 20 participants who attended the program, they mostly could understand, although there was still a need to follow up the training to improve understanding.Keywords: Product Quality, Financial Management, Business Mental